Legal Implications of Coercive Success Fee Demands by Attorneys Promising Victory Before Case Resolution - Pramudita, Laurentius Ervin Ricky; Sari, Retno Dewi Pulung (Reformasi Hukum, 2024)
The practice of coercively demanding a success fee by lawyers who promise victory to clients before a case is resolved raises serious legal and ethical concerns. This study aims to examine the legal implications of such actions and their relation to violations of the Code of Ethics for Advocates. The research employs a normative legal method with a qualitative juridical approach, using library research on primary and secondary legal materials. The findings indicate a shift in values within the legal profession from a socially driven service to a profit-oriented practice which reflects a degradation of lawyers' social responsibility in providing non-commercial legal assistance. A success fee is, in principle, a legitimate additional compensation if agreed upon professionally and paid after the case has concluded. However, promising a favorable outcome before resolution and using it as a means to demand payment constitutes a breach of ethical standards. The study concludes that lawyers who guarantee case outcomes and coercively demand success fees are in serious violation of professional ethics and may be subject to both ethical and legal sanctions. It is recommended that the advocate professional bodies reinforce ethical supervision mechanisms and provide continuous legal ethics training to prevent such practices.